Moral Attention and Bad Sentimentality - Jamieson, Lesley (Springer, 2025)
In this paper, I challenge standard views of the moral badness of sentimentality defended by art critics and philosophers. Accounts based on untruthfulness and selfindulgence lack the resources to both explain the badness of bad sentimentality and to allow that there are benign instances. We are sometimes permitted to be sentimental even though it is self-serving. A non-moralistic account should allow for this. To provide such an account, I frst outline a substantive view of the ideal of unsentimentality by turning to Rainer Maria Rilke’s Letters on Cézanne. Rilke celebrates the artist for his unsentimental love of his subjects and “untiring objective wakefulness” to them. I then turn to Iris Murdoch’s ethics of attention (itself infuenced by Rilke) to explain why this ideal is so difcult to live up to in practice, the various ways that we fall short, and what our failures mean. What Murdoch contributes is both a sense that the lovingly attentive attitude that Rilke describes is morally—and not just artistically—important and a compassionate account of the human egocentrism that inhibits it. By thinking of sentimentality as a failure of moral attention, we can appreciate how particular instances difer from one another. Sentimentality can console us in difcult times or can gratify our egos; it can be a form of escapism or can rigidly enclose reality; and it can be harmlessly self-serving or a selfsh failure to morally attend to the other when it counts. I conclude by outlining some ways that being seen with Cézanne-like moral attention can matter to us.
Keywords: Iris Murdoch; Rilke; Ethics of attention; Sentimentality; Fantasy; Philosophy of love; Paternalism; Selfshness